Seroprevalence of Human Fascioliasis in Chaharmahal and Bakhtiyari Province, Southwestern Iran - Kouroush MANOUCHEHRI NAEINI; Farnaz MOHAMMAD NASIRI; Mohammad Bagher ROKNI; Soleiman KHEIRI (Iranian Journal of Public Health, 2016)
Background: Fascioliasis caused by Fasciola hepatica and F. gigantica is a foodborne and waterborne zoonotic disease with a worldwide distribution. The illness occurs in regions with intensive sheep or cattle production. In some parts of Iran the incidence of human infection has increased over the past decades. Since Chaharmahal and Bakhtiyari Province has been known as a main pole of traditional animal husbandry and there was no information about human fascioliasis in this region, the present study was carried out on human population to determine the seroprevalence of this infection.